2015
DOI: 10.2147/rsrr.s66645
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of robot-assisted laparoscopic radical prostatectomy in high-risk prostate cancer patients: experience in 34 patients with oncologic and functional outcomes

Abstract: Introduction:In this retrospective study, we report outcomes of robot-assisted laparoscopic radical prostatectomy (RARP) in high-risk prostate cancer (HRPC) classified according to a D'Amico risk group with minimum 1-year follow-up. Methods: A total of 34 patients who had at least one preoperative HRPC feature and who underwent RARP were included. Mean patient age and preoperative serum prostate-specific antigen levels were 62.6±6.4 years and 12.2±9.1 ng/mL, respectively. Preoperatively, two (5.8%), one (2.9%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…With current surgical techniques, trifecta and pentafecta rates were 38 and 26 %, respectively [8], even in high risk cancer patients. Whilst some papers have shown that not all patients undergoing robot-assisted procedures with compete excision of the neurovascular bundle will become impotent (20 % had an erection sufficient for penetration), this is a rarity [9].…”
Section: Intraoperative Techniques To Improve Erectile Functionmentioning
confidence: 99%
“…With current surgical techniques, trifecta and pentafecta rates were 38 and 26 %, respectively [8], even in high risk cancer patients. Whilst some papers have shown that not all patients undergoing robot-assisted procedures with compete excision of the neurovascular bundle will become impotent (20 % had an erection sufficient for penetration), this is a rarity [9].…”
Section: Intraoperative Techniques To Improve Erectile Functionmentioning
confidence: 99%
“…We have previously published results from our initial robot-assisted radical prostatectomy (RARP) case series in HRPC. 15 In the current study, we report mid-term functional and oncological results from our contemporary RARP case series in HRPC.…”
Section: Introductionmentioning
confidence: 99%
“…With current surgical techniques, trifecta (oncological control, continence and erectile function outcomes) and pentafecta rates were 38% and 26%, respectively [9], even in high risk cancer patients. Whilst some papers have shown not all patients undergoing robotassisted procedures with compete excision of the neurovascular bundle will become impotent (20% had an erection sufficient for penetration), this is a rarity [10].…”
Section: Introductionmentioning
confidence: 99%